Health behaviors of patients with arterial hypertension aged 60-70 treated in the cardiology department - Bąk, Ewelina; Piętka, Jadwiga; Pawlak, Anna (Journal of Education, Health and Sport, 2023)
Introduction and purpose of the study: Arterial hypertension is currently the biggest economic problem among cardiovascular diseases. It concerns the population of the elderly, in whom health behaviors are necessary, but difficult to implement. Hospitalization of such patients creates an opportunity for education and preventive actions in the field of proper health behavior. Materials and methods: The study used the diagnostic survey method and the self-questionnaire was used in conjunction with the standardized questionnaire of the Health Behavior Inventory. The research was conducted in the Cardiology Department, among 100 patients hospitalized in the period from August to October 2019. The study was approved by the management of the Provincial Hospital in Bielsko-Biała. Research results: In the study group of patients with arterial hypertension, the highest score among health behaviors was given to health practices and positive mental attitude, and the lowest score was given to preventive behaviors. Conclusions: Declared health behaviors among patients with arterial hypertension were statistically significantly higher among women, people who do not work, eat a healthy diet, avoid stress, maintain physical activity, regularly take medications, regularly cooperate with a family doctor and use an adequate amount of sleep and rest.